Developmentalism and the Genocide–Ecocide Nexus. Issue 2 (3rd April 2021) - Crook, Martin; Short, Damien
ABSTRACT: This article seeks to contribute to an emerging "ecological turn" in genocide studies that places the material "extra-human environment" at the core of the biological and cultural integrity of social groups such as indigenous peoples and territorially dependent placed-based groups. Such social groups are often the victims of an array of ecological and culturally genocidal coercive practices which we will discuss herein. From land grabs in the service of economic development projects in Australia to, perversely, "conservation" and the "environmental" protection projects in Uganda and Kenya. For many indigenous and place-based peoples, their historical narrative and their practises, rituals and traditions are inextricably connected to their land base. In this article we explore the ecologically induced genocide suffered by such groups where environmental destruction results in conditions of life that fundamentally threaten a social group's cultural and/or physical existence.